Ratio As A Worldview Benchmark: From Mystifikation To Objectivity - Стежко, З. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2019)
A necessity of studying of historical worldview kinds with an aim of a formation an optimal, worldviewable orientation of public processes to supply social progress has being justified in this study. In the introduction the author depicts a public crisis situation, which appeared while crossing from postmodern to postpostmodern ideology. The aim of the study is a comparison of considerations regarding the fate of rationalism and irrationalism, substantiation of methodological, conceptual guidelines on the prospects of postmodern humanism and the limits of their effectiveness. The task is to carry out a philosophical analysis of the content of rationality in the sociocultural sphere of postmodernism, the potentials of irrational forms of cognition, ways of typologizing rationality and its perspective. Research method is rational philosophy, because it provides the maximum depth of human cognitive capacity. Operating a system of categories (freedom-necessity, essence-phenomenon, content-form, system-structure-element, etc.), which are based on the principles of objectivity, rationality, determinism, reflection, laws of formal and dialectical logic, rational philosophy as a methodology requires their consistent, constant adherence to all stages of cognition and practical implementation. Research results: in a postmodern period positive changes in society have occurred: the boundaries of freedom and mutual understanding have expanded; but ignoring objective truth, reason, the absolutization of subjectivity has great negative consequences. Philosophical postmodern project, in fact, tried to realize an illusory picture of the world and that has become a big problem for today. It is proved that irrationalism cannot be at the center of worldview and methodology. And if its objective-substantial aspects will be abstracted from the mind, then, in fact, there will be nothing to control mental activity; there will be a thinking process that is changing arbitrarily in accordance with our whims. We have come to the following in discussion: the objective global thinking exclusively as an extremely abstract spiritual “framework” can carry out the spiritual “guidance” of human activity; that must be transformed into a philosophical methodology of interpretation, understanding, explanation, prediction and forecast of reality. Conclusions: the global thinking as overall, unique brain could become the centre of dominant worldview. Herewith it gives an opportunity of developing for a different, irrational, subjective appearing in human matter-but only for bright frameworks of mind.